The witch's boy - Barnhill, Kelly (London : Piccadilly Press, 2020)
A stunning novel from the Newbery Medal winning and New York Times bestselling author of THE GIRL WHO DRANK THE MOONWhen Ned and his identical twin brother tumble from their raft into a raging river, only Ned survives.
Keywords: Children's stories, Fantasy fiction, Fiction